Iraqi household cockroaches collected from Diyala Province are potential vectors of medically-important parasites - ALGAILANY, Maryam; ALHADIDI, Sanaa; MOLAN, Abdul-Lateef (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Household cockroaches constitute a significant public health threat due to their capacity of transmitting medically-important parasites and other pathogens. The role of Iraqi household cockroaches as potential vectors of medically-important parasites was evaluated in the present study. Fifty cockroaches (Periplaneta americana) were collected from different dwelling places of Baquba City, Diyala Province during the period from October to December 2022. The contents of their guts and external body surfaces were examined for the presence of medically-important parasites. The overall prevalence rate of parasitic infestation on the external body surfaces was 60.0%, while the overall prevalence rate of parasitic infection in the guts was 56.0%. Based on capture sites, cockroaches trapped in the toilets had more parasites than those caught from kitchens and rooms. Four species of medically important parasites were isolated from the external body surfaces of the cockroaches; three species were identified as protozoa and only one species was helminth. The protozoan parasites were identified as Blastocystis spp. (36.0%), Giardia spp. (14.0%) and Cryptosporidium spp. (4.0%). In addition, five species of medically important parasites were isolated from the gut contents; four species were identified as protozoa and only one species was helminth. The protozoan parasites were identified as Blastocystis spp. (24.0%), Giardia spp. (10.0%), Cryptosporidium spp. (8.0%), and Entamoeba histolytica/ E. dispar (2.0%). Enterobius vermicularis was the only helminth parasite isolated from both gut contents (2.0%) and external body surfaces (2.0%). In conclusion, the results showed that cockroaches were found to harbor intestinal parasites of public health importance and awareness on the potential role of these insects in the transmission of human intestinal parasites needs to be established